2014
DOI: 10.1007/978-1-4939-1782-2_2
|View full text |Cite
|
Sign up to set email alerts
|

About the (Non)scalar Property for Time Perception

Abstract: Approaching sensation scientifically is relatively straightforward. There are physical attributes for stimulating the central nervous system, and there are specific receptors for each sense for translating the physical signals into codes that brain will recognize. When studying time though, it is far from obvious that there are any specific receptors or specific stimuli. Consequently, it becomes important to determine whether internal time obeys some laws or principles usually reported when other senses are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 78 publications
7
56
0
5
Order By: Relevance
“…Interestingly, research contesting the constancy of CVs traditionally shows an increase in CV with longer/supra-second timed durations (also see Grondin, 2014, for a review); although higher CVs have been found for sub-second intervals as well (see Lewis & Miall, 2009). Our results in all three experiments contradict these findings, showing that CVs decrease with target durations (see above).…”
Section: Discussionsupporting
confidence: 40%
“…Interestingly, research contesting the constancy of CVs traditionally shows an increase in CV with longer/supra-second timed durations (also see Grondin, 2014, for a review); although higher CVs have been found for sub-second intervals as well (see Lewis & Miall, 2009). Our results in all three experiments contradict these findings, showing that CVs decrease with target durations (see above).…”
Section: Discussionsupporting
confidence: 40%
“…Although the idea of a dual-process approach is compatible with the interpretation of unequal Weber fractions in some timing tasks (Grondin, 2012; for reviews, see Gibbon et al, 1997, or Grondin, 2014, what we suggest here is to interpret the results obtained in the present study from a very different perspective-that is, that of a limitation in short-term memory. What is sometimes simply attributed to inattention may rather be due to an inherent temporal capacity.…”
Section: Discussionmentioning
confidence: 75%
“…Either we assume that in condition High‐Low the pigeons continued to time the moment of reversal, and then conclude, from the extremely low coefficients of variation, that they violated the scalar property of timing (Gibbon, ), or we assume that local cues, rather than time, controlled switching. Given the generality of the scalar property, the latter hypothesis seems more plausible and parsimonious (but for violations of the scalar property see Bizo, Chu, Sanabria, & Killeen, ; Grondin, ; and Zeiler & Powell, ). For some reason, then, in condition High‐Low, switching came under the control of local cues, namely the food/no food outcomes of S1 choices.…”
Section: Discussionmentioning
confidence: 99%